Pseudo-aneurysm of Distal Aortic Stump – A Manifestation of Aortoenteric Fistula - Jaafar, Mohd Najib (Journal Of Cardiovascular, Neurovascular & Stroke, 2023)
Background: Secondary aortoenteric fistula (AEF) is rare but devastating complication of abdominal aortic reconstruction surgery for aortic aneurysm. Most patients presented with acute upper gastrointestinal bleeding. CTA abdomen is usually performed to attain the diagnosis. However, AEF has invariable appearances on CT where mostly are non-specific and similar to perigraft infection (PGI). A case of secondary AEF following multiple series of aortic surgery, with CT manifestation of recurrent pseudo-aneurysm of aortic stump, is presented. Case Presentation: 65 years old man who had undergone series of aortic reconstructive surgery for infra-renal abdominal aortic aneurysm presented acutely for hematemesis and per rectal bleeding. Initial CTA abdomen revealed pseudoaneurysm of the distal aortic stump, which was successfully embolized with coils. However, the symptoms recurred and repeated CTA showed new pseudo-aneurysm but no typical findings of AEF. Emergency laparotomy confirmed AEF at duodenojejunal junction that was repaired with primary closure. Unfortunately, patient died 3 days later due to multiple post-operative complications. Conclusion: Presence of pseudo-aneurysm with background of perigraft infection should raise the suspicion of AEF, especially in patients with history of aortic intervention that presented with gastro-intestinal bleeding. CTA abdomen is invaluable in providing the diagnosis of AEF despite its variable manifestations.